2019
DOI: 10.1186/s40248-019-0174-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of patients with severe acute respiratory infections (SARI): results from the Egyptian surveillance study 2010–2014

Abstract: Background Respiratory viral and atypical bacterial infections data in Egyptian patients are sparse. This study describes the clinical features and outcomes of patients with severe acute respiratory infections (SARI) in hospitalized patients in Egypt. Methods SARI surveillance was implemented at Cairo University Hospital (CUH) during the period 2010–2014. All hospitalized patients meeting the WHO case definition for SARI were enrolled. Nasopharyngeal/oropharyngeal (NP/O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
34
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 25 publications
7
34
2
Order By: Relevance
“…One might expect that the presence of medical comorbidities will put SARI patients into higher risk for severe disease and ICU admission. In this respect, it was also disappointing and contradicting other studies [11,15,17], as it was observed that-in terms of comorbidities-there were no significant differences between ICU and non-ICU SARI patients. Definitely, studies with larger numbers of patients are needed to clarify these associations.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…One might expect that the presence of medical comorbidities will put SARI patients into higher risk for severe disease and ICU admission. In this respect, it was also disappointing and contradicting other studies [11,15,17], as it was observed that-in terms of comorbidities-there were no significant differences between ICU and non-ICU SARI patients. Definitely, studies with larger numbers of patients are needed to clarify these associations.…”
Section: Discussionmentioning
confidence: 65%
“…We have recently published the largest surveillance Egyptian study that addressed the epidemiological patterns of SARI due to viruses in both children and adult population and their relation to the clinical characteristics and outcomes of those patients [11]. Despite that viral pathogens were encountered in one-third of SARI patients, these infections had no negative impacts on clinical features, clinical course, and outcomes of those patients [11]. In this related study, we aimed to address the impacts of SARI on the clinical outcomes of patients admitted to the ICU, in terms of morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also a study conducted in Chilie found that adults are more prone to SARI when they suffered from cardiac and respiratory illnesses (5). An Egyptian study survey was conducted recently in Assuit and included pediatric and adult groups from 2010-2014 by Hatem et al,they found that 53% of patients had co-morbidities mostly in adults not children, and in the form of chronic lung diseases 43% (21).…”
Section: Discussionmentioning
confidence: 99%
“…The second study, which was published 2019 and was done from the period 2010-2014, at Cairo University Hospital, showed an incidence rate viral respiratory viruses in Egypt of 33.5% in hospitalized adult and paediatric Egyptian patients with SARI 63 .…”
Section: Discussionmentioning
confidence: 99%